Diabetic retinopathy in type two diabetic patients: Epidemiology and modern view on the pathogenesis. Review - I. V. Vorobieva; D. A. Merkushenkova (Oftalʹmologiâ, 2014)
Development of late microvascular complications — diabetic retinopathy, nephropathy and neuropathy — in type 2 diabetic pa- tients is associated with higher invalidization risk and lethality. Diabetic retinopathy is the leading cause of blindness in people of work- ing age in developed countries. Classical approach to diabetic retinal damage pathogenesis is widened and considered at the molecular level in terms of cell interactions during angiogenesis. In this literal review the actual epidemiological data is presented along with therole of angiogenic factors in diabetic retinopathy and maculopathy pathogenesis.